Повышение экономичности ударных пневмоагрегатов за счёт рационального управления контуром питания - Атаманов, Ю. Л.; Крутиков, Геннадий Анатольевич; Стрижак, Марьяна Георгиевна (НТУ "ХПИ", 2013)
Розглянуті схеми використання пневмоагрегата з вбудованим резервуаром. Запропоновано схему керування ударним пневмоциліндром, що дозволяє значно поліпшити всі найважливіші експлуатаційні показники агрегату: ступінь енергетичної досконалості, довговічність за рахунок безударної посадки поршня в сідло при зворотному ході, зниження браку при виконанні ударних операцій в результаті відсутності повторних ударів, ступінь безпеки внаслідок безударного спрацьовування в разі відсутності заготовки.

The schemes are considered using pneumounit with built-in reservoir. The scheme of management by the shock pneumatic cylinder, allowing considerably to improve all most important operational indicators of the unit is offered: degree of power perfection, durability at the expense of unaccented landing of the piston in a saddle at reverse motion, decrease in marriage when performing shock operations as a result of lack of repeated blows, safety degree owing to unaccented operation in case of lack of preparation.
Improving economy impact pneumounit through judicious management of the power supply circuit
Keywords: пневмоагрегаты; ударный пневмоцилиндр; энергосбережение; пневмоприводы; приводы кузнечных молотов